1966
DOI: 10.1002/jcp.1040670409
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of immunoglobulin synthesis

Abstract: The genetics of immunoglobulins (Ig) has been discussed from the standpoint of the determinism of the antigenic specificities of different kinds that they carry: isotypic specificities, which are uniform in all indviduals of the same animal species; allotypic specificities, which are not the same in all individuals, but are uniform within groups of individuals; idiotypic specificities, each of which not only is particular to the antibody against one given antigen but is, in addition, variable with individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

1969
1969
1984
1984

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(27 citation statements)
references
References 101 publications
0
27
0
Order By: Relevance
“…Among the antigenic specificities of several kinds that are distinguished in immunoglobulins, the isotypic and allotypic specificities apparently reflect differences in primary structures (6,7). It seems reasonable to assume that the same is true for idiotypic specificities, and in addition, that the structural differences concerned in the latter case are located in the variable regions of the polypeptide chains.…”
Section: Speculation On the Relationship Of Idiotypy To The Primary Smentioning
confidence: 99%
See 1 more Smart Citation
“…Among the antigenic specificities of several kinds that are distinguished in immunoglobulins, the isotypic and allotypic specificities apparently reflect differences in primary structures (6,7). It seems reasonable to assume that the same is true for idiotypic specificities, and in addition, that the structural differences concerned in the latter case are located in the variable regions of the polypeptide chains.…”
Section: Speculation On the Relationship Of Idiotypy To The Primary Smentioning
confidence: 99%
“…Its serum, taken before the latter immunization, was no longer precipitated by the antiidiotypic serum against its anti-S, typhi antibodies. The serum samples taken after the immunization against S. typhimurium were precipitated by the same 6 We want to thank Doctor L. Le Minor, chef du Service des Enterobact~riac~es de l'Institut Pasteur, to whom is due the choice and supply of a Salmonella fulfilling these requirements: S. tranoroa (22).…”
Section: Comparison Of the Idiotypic Specific Ties O] The Antibodies mentioning
confidence: 99%
“…(Received for publication 27 September 1972) In the rabbit, b locus allotypic determinants present on kappa-type light chains have been demonstrated both on circulating immunoglobulins (1,2) and on the membrane-associated immunoglobulins of bone marrow-derived (B) 1 lymphocytes (3)(4)(5)(6). The production of circulating b5 immunoglobulin (Ig) can be suppressed by exposing rabbits in utero or at birth to anti-b5 antisera (allotype suppression) (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…This idiotypic variation has been studied extensively in mice and rabbits. As early as 1963, antigenic determinants located on V regions of rabbit IgH chains were found (10). Pedigree analysis of rabbits homozygous for two different VH region allotypes demonstrated that VH and CH region allotypes were linked, although recombinants were observed (11).…”
mentioning
confidence: 99%